Coronado, Wichita County - Harkness, Steve (Kansas State University, The Chapman Center for Rural Studies, 2013)
I am writing this paper to show people some of the history of Wichita County, Kansas. I am also writing about how “wild” the West really was when people were migrating out to the newly formed state of Kansas. This paper includes newspaper accounts from the week after the county seat fight and has photographs of structures in each town; I also show how Leoti and Coronado look today. This paper is the story of how Coronado started and ended in the blink of an eye.
Steve Harkness, “Coronado, Wichita County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/119.
Keywords: Coronado; Highway 96; Wichita County; William Rains; Hotel Vendome; Kansas & Oklahoma Railroad